The cost of job loss in carbon-intensive sectors: Evidence from Germany - Barreto, Cesar (OECD Publishing, 2023)
The green transformation of the economy is expected to lead to a sharp reduction in employment in carbon-intensive industries. For designing policies to support displaced workers, it is crucial to better understand the cost of job loss, whether there are specific effects of being displaced from a carbon-intensive sector and which workers are most at risk. By using German administrative labour market data and focusing on mass layoff events, we estimate the cost of involuntary job displacement for workers in high carbon-intensity sectors and compare it with the displacement costs for workers in low carbon-intensity sectors. We find that displaced workers from high carbon-intensity sectors have, on average, higher earnings losses and face stronger difficulties in finding a new job and recovering their earnings. Our results indicate that this is mainly due to human capital specificity, the regional clustering of carbon-intensive activities and higher wage premia in carbon-intensive firms. Workers displaced in high carbon-intensity sectors are older, face higher local labour market concentration and have fewer outside options for finding jobs with similar skill requirements. They have a higher probability to switch occupations and sectors, move to occupations that are more different in terms of skill requirements compared to the pre-displacement job, and are more likely to change workplace districts after displacement. Women, older workers and those with vocational degrees as well as workers in East Germany, experience particularly high costs in case they are displaced from high carbon-intensity sectors
Keywords: Employment; Economics; Germany